Disaster Literacy and Mitigation Education: Global Trend and Future Directions for Developing Disaster Mitigation-based Science Learning Model - Amini, Risda; Helsa, Yullys; Bachri, Syamsul; Yosritzal, Yosritzal; Suparman, Suparman; Erita, Yeni; Wijanarko, Tiok (Migration Letters, 2024)
The publication trend regarding disaster literacy studies and its mitigation education has been moderately growing in the last decade. Systematic review studies, however, providing comprehensive review related to this topic has not been carried out nor also reported in the electronical journals or conference proceedings. A systematic review combining between bibliometric analysis, meta-analysis, and meta-synthesis was used to describe the profile of students’ disaster knowledge, examine the effect of disaster mitigation education on disaster knowledge, and present global trends and future directions for developing disaster mitigation-based science learning model. 1,284 eligible documents from Scopus database and 24 specifically eligible documents from Google Scholar published in 2014 – 2023 were used as the data. Results showed that between 2014 and 2023, publication trend of disaster literacy studies and its mitigation education slightly increased, whereas citation trend on the documents relatively fluctuated. At least there were some main emerging themes regarding this topic, such as disaster type, country which often happened disaster, learning environment in disaster mitigation education, the ways to mitigate disasters, methodology, and disaster & its mitigation. Additionally, disaster mitigation education had significantly positive strong effect (g = 2.615; p < 0.05) on students’ disaster knowledge. Moreover, overall, students had enough disaster knowledge. This recent study implies that the development of disaster mitigation-based science learning model can be performed by implementing some phases, such as: (1) situation concept, (2) mitigation practices, (3) knowledge of evacuation routes, and (4) cooperation in mitigation practices.